Szathmári Paksi József élete és munkássága - BÁTORINÉ MISÁK, Marianna (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
Life and Work of József Paksi Szathmári. József Szathmári Paksi was the sixth bishop of the Reformed Diocese of Tiszáninnen. He was born in Sajókazinc on 1763. After his studies, he worked as a pastor. Initially, he served as a chaplain with his father, Ábrahám Szathmári Paksi, in Mezőkeresztes. He began his independent pastoral career in Szikszo, and in 1790, when the Reformed congregation of Miskolc invited him, he continued his work there. During his time as pastor in Miskolc, he was first elected dean of the Borsod Diocese in 1817 and later, in the same year, became the chief notary of the church district. In 1820, he was appointed as deputy bishop alongside the ailing Gábor Fülep Őri. After Őri’s death, he was promoted to ordinary bishop without the need for an election. In 1830, the Theological Faculty of the University of Göttingen awarded him an honorary doctorate on the occasion of the 300th anniversary of the Augsburg Confession. The Emperor initially refused to allow him to use the foreign-awarded doctorate, and only after several petitions did he receive it in 1846. He faithfully carried out his pastoral and episcopal duties. He served the Miskolc congregation for fifty-eight years, an unparalleled period. During this time, he tirelessly worked on building, developing, and improving the congregation and its institutions, including the church, schools, hospital, and mill. At the same time, he did not neglect his own academic development, making him one of the most qualified pastors of his time.